2023
DOI: 10.3390/nu15071641
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Adults: Position Statement of Polish Association for the Study on Obesity, Polish Association of Endocrinology, Polish Association of Cardiodiabetology, Polish Psychiatric Association, Section of Metabolic and Bariatric Surgery of the Association of Polish Surgeons, and the College of Family Physicians in Poland

Abstract: Obesity in adults and its complications are among the most important problems of public health. The search was conducted by using PubMed/MEDLINE, Cochrane Library, Science Direct, MEDLINE, and EBSCO databases from January 2010 to December 2022 for English language meta-analyses, systematic reviews, randomized clinical trials, and observational studies from all over the world. Six main topics were defined in the joint consensus statement of the Polish Association for the Study on Obesity, the Polish Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…Obesity has emerged as a global epidemic in recent decades, presenting a significant public health challenge. Epidemiological studies have revealed alarming trends, with obesity rates steadily rising across the world [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has emerged as a global epidemic in recent decades, presenting a significant public health challenge. Epidemiological studies have revealed alarming trends, with obesity rates steadily rising across the world [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis of longitudinal studies by Luppino et al [76], baseline depression (symptoms and disorder) increased the odds of developing obesity. Therefore, patients with obesity should be screened for depression, and patients diagnosed with depression should have their body mass monitored [77].…”
Section: Depressionmentioning
confidence: 99%
“…These include changes in dietary habits, such as elevated intake of energy-dense and processed foods. Mass production has led to a significant decrease in the quality of food products [3]. According to the analysis of energy consumption in 167 countries conducted in 2018, Poles were ranked 10 th [4].…”
Section: Introductionmentioning
confidence: 99%